Lost it at the produce counter. - Trotter, Robert J. (Psychology Today, 1985)
Johns Hopkins University psychologist John Hart, Jr., and his colleagues got a rare opportunity to study how the brain organizes language when they examined and tested M.D., a patient who suffered a stroke in 1981 that left him with global aphasia, the inability to use or comprehend words. Although he had almost totally recovered in about eighteen months, M.D. still had difficulty in naming fruits and vegetables. The researchers concluded that M.D. was suffering from a “selective disturbance” in his brain's semantic system. M.D. could point correctly to pictures of fruits and vegetables after hearing their names and could also categorize the written names of fruits and vegetables, although he could not correctly categorize their pictures. The researchers reported on M.D. in Nature, Vol. 316, No. 6027.